Text Presentation and Reading Skills Development: A Script-Combinatory Alternative to Dyslexic Tendencies in Francophone Primary School Children in Cameroon - Yannick, TAMO FOGUE (International Journal on Integrated Education, 2023)
This study compares the advantages of cursive and scriptural presentation (Gong Nota Flores) of text in learning to read. As part of the typological analysis of teaching approaches by Goigoux (2004), she predicts the effectiveness of script-syllabic, script-global and script-combinatorial alternatives. Empirically, an experiment was carried out with 450 children of the second year elementary school in the department of Koung-Khi (West-Cameroon). It follows that the graphological presentation, both in the graphophonological/global approach as well as the phonographic/phonic/syllabic and combinatorial/mixed approach, has more advantage for the teaching/learning of reading a text configured in script (Gong Nota Flores), only in cursive. And the present article proposes it as the best psycho-pedagogical alternative to the dyslexic tendencies increasingly observed in children of French-speaking primary schools in Cameroon.